Effects of glucagon like peptide-1 receptor agonists, sodium-glucose cotransporter-2 inhibitors and their combination on vascular function and myocardial work index in patient with type-2 diabetes. (25th November 2020) - Ikonomidis, I; Pavlidis, G; Thymis, J; Birba, D; Kalogeris, A; Kousathana, F; Kountouri, A; Balampanis, K; Parissis, J; Andreadou, I; Katogiannis, K; Dimitriadis, G; et al.
Abstract: Background/Introduction: Type-2 diabetes mellitus (T2DM) is associated with endothelial and myocardial dysfunction. Purpose: We investigated the effects of insulin, glucagon like peptide-1 receptor agonists (GLP-1RA), sodium-glucose cotransporter-2 inhibitors (SGLT-2i) and their combination on vascular and cardiac function of T2DM patients. Methods: A hundred-sixty T2DM patients were randomized to insulin (n=40), liraglutide (n=40), empagliflozin (n=40) or their combination (GLP-1RA+SGLT-2i) (n=40) as add-on to metformin. We measured at baseline, 4 and 12 months post-treatment: a) perfused boundary region (PBR) of the sublingual arterial microvessels (marker of glycocalyx thickness), b) pulse wave velocity (PWV), central systolic blood pressure (cSBP), c) global LV longitudinal (GLS), circumferential (GCS) and radial (GRS) strain, d) the ratio PWV/GLS, as an index of ventricular-arterial interaction, e) myocardial work index (GWI) using speckle tracking imaging. Results: Twelve months post-treatment, all patients improved PBR, PWV, GLS, GCS and GRS (p<0.05). GLP-1RA, SGLT-2i and their combination showed a greater reduction of PBR, PWV and cSBP than insulin, despite a similar HbA1c reduction (p<0.05). GLP-1RA or GLP-1RA+SGLT-2i provided a greater decrease of PWV/GLS (28.1% and 31% vs. 11.1% and 14.5%) and a greater increase of GWI (12.7% and 17.4% vs. 3.1% and 2%) compared with insulin or SGLT-2i. SGLT-2i or GLP-1RA+SGLT-2i showed a greater decrease of PWV (10.1% and 13%), cSBP than insulin or GLP-1RA (PWV: 3.6% and 8.6%) (p<0.05 for all comparisons) (Table 1). The dual therapy showed the greatest effect on measured markers in patients with LVEF <55% (p<0.05). Conclusions: Twelve-month treatment with GLP-1RA, SGLT-2i and their combination showed a greater improvement of vascular markers and effective cardiac work than insulin in T2DM. The combined therapy was superior to either insulin, or GLP-1RA and SGLT-2i separately. Funding Acknowledgement: Type of funding source: None